132 Intra-abdominal Fibromatosis with Subsequent Development of Lower Extremity Multifocal Tumors—Is Chronic Lymphedema or Mosaicism a Risk Factor for Recurrence and Multifocality?. (11th January 2018) - Hu, Yan; Raza, Anwar; Choo, Evelyn
Abstract: Introduction: Fibromatosis is a rare, benign slow-growing infiltrative tumor with a propensity for local recurrence. The etiology is largely unknown, but it is associated with Gardner syndrome, and has several risk factors, including previous trauma, surgery, pregnancy, and prolonged estrogen intake. Case Presentation: Here we report a case of fibromatosis of the right pelvis with local recurrence and multifocal tumors in the distal ipsilateral lower extremity in the setting of post-surgical severe chronic lymphedema. The patient is a 28-year-old black woman with a history of two prior C-sections who presented three years later with a large mass occupying the right side of the pelvis with compression of the right external iliac vessels. No mesenteric or colonoscopic evidence of Gardner syndrome was identified. Her only known risk factors were the two previous C-sections. The resected 16.5 cm mass was adherent to the pubic symphysis, pubic rami, and right femoral vessels, with multiple microscopically positive margins. The patient subsequently developed lymphedema of the right lower extremity and a recurrent 6.6 cm right pelvic mass a year later. Five years after her initial resection, she developed synchronous 10 cm right upper calf and 7 cm right ankle masses, which were biopsied and confirmed to be fibromatosis. Her limb tumors show rare cells with stippled nuclear beta-catenin staining. Discussion: Fibromatosis is known to be locally recurrent; our case raises the question of whether chronic lymphedema is a risk factor for distal downstream tumor development vs possible presence of right-sided lower body mosaicism with beta-catenin gene mutation.